Identificamos y establecemos la relacin entre convivencia social y ayuda social - Gamboa Cueva, Leslie Marisol (2022)
Social coexistence and social assistance are essential complementary elements for the establishment of healthy relationships between individuals in any society, learning to live together implies knowing how to work cooperatively in a permanent framework of respect and tolerance, taking into account the interests and objectives of others. based on developing projects that generate benefits for all._x000D_ Hence, the need arises for this professional sufficiency work entitled: "We identify and establish the relationship between coexistence and social help", which was developed for second-year high school students, in the area of Personal Development, Citizenship and Civics, and its purpose was to identify and establish the relationship between coexistence and social help for the self-training and interaction of the human being._x000D_ Throughout the chapters, the theoretical support is presented to understand the main aspects of the topic to be developed and the psyco-pedagogical support to know the pedagogical and didactic processes that are carried out in a significant learning experience.